Reading‐Related Causal Attributions for Success and Failure: Dynamic Links With Reading Skill. Issue 1 (29th April 2017) - Frijters, Jan C.; Tsujimoto, Kimberley C.; Boada, Richard; Gottwald, Stephanie; Hill, Dina; Jacobson, Lisa A.; Lovett, Maureen W.; Mahone, E. Mark; Willcutt, Erik G.; Wolf, Maryanne; Bosson‐Heenan, Joan; Gruen, Jeffrey R.
Abstract: The present study investigated the relation among reading skills and attributions, naming speed, and phonological awareness across a wide range of reading skill. Participants were 1, 105 school‐age children and youths from two understudied populations: African Americans and Hispanic Americans. Individual assessments of children ranging in age from 8 to 15 years were conducted for reading outcomes, cognitive and linguistic predictors of reading, and attributions for success and failure in reading situations. Quantile regressions were formulated to estimate these relations across the full skill span of each outcome. Reading‐related attributions predicted contextual word recognition, sight word and decoding fluency, and comprehension skills. Attributions to ability in success situations were positively related to each outcome across the full span. On three reading outcomes, this relation strengthened at higher skill levels. Attributions to effort in success situations were consistently and negatively related to all reading outcomes. The results provide evidence that the strength of the relation between reading and attributions varies according to reading skill levels, with the strongest evidence for ability‐based attributions in situations of reading success.